Institutional Arrangements and Fiscal Performance: The Latin American Experience - Ernesto H. Stein; Ernesto Talvi; Alejandro Grisanti (Inter-American Development Bank, Office of the Chief Economist, 1998)
This paper considers whether institutional factors, in this instance electoral systems and procedures, affect Latin American countries` fiscal performance as measured by the size of the public sector, fiscal deficits, the size of the public debt, and the degree of procyclality of fiscal policy. The authors find that electoral systems characterized by large district magnitude and high political fragmentation have larger governments, larger deficits, and more procyclical fiscal policies. Transparent and hierarchical budget procedures, on the other hand, lead to lower deficits and levels of debt.
Keywords: 330